(untitled) (Annals of Medical Research, 2021)
Aim: Although chronic inflammatory rheumatic diseases (CIRDs) primarily affect the joints due to arthritis; involvement of other systems and organs is not rare. Ultrasound evaluations are particularly useful in the detection of pathologies observed in the gastrointestinal tract. The aim of this study was to investigate and compare the results of abdominal ultrasonography in gastrointestinal system of some common chronic inflammatory rheumatic diseases.Material and Methods: 96 patients with rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis were included in the study. The data of patients were retrospectively reviewed from patient files and hospital database. Patients with abdominal ultrasound performed for the check-up indication in the last 6 months and updated laboratory tests in the last 1 month were included in the study. The patients were divided into three groups according to the diagnosis and the results were compared.Results: No gastrointestinal system involvement was observed in the patients except liver and gallbladder pathologies. The most frequent liver pathologies were hepatosteatosis (49.0%) and hepatomegaly (41.7%), respectively. The rate of patients with cholecystectomy was 8.3% and 6.3% of the patients had gallstones. When the results were compared between the groups, it was seen that only the incidence of gallstones was significantly higher in the psoriatic arthritis group than in other groups.Conclusion: In the course of chronic inflammatory rheumatic diseases, many organ and system involvement may be observed. Abdominal ultrasound imaging, especially in patients with additional risk factors, may be useful for early detection of many intra-abdominal organ pathologies, especially the gastrointestinal tract.